Synthesis of star PMMA via ARGET ATRP towards application in acrylic bone cements. Issue 1 (29th March 2021) - Tham, Do Quang; Huynh, Mai Duc; Dung, Nguyen Thi Kim; Van Cong, Do; Huyen, Lai Thi; Linh, Nguyen Thi Dieu; Thai, Nguyen Thi; Son, Nguyen Anh
Abstract: In this study, we attempted to apply a four‐arm star poly(methyl methacrylate) (4sPMMA) as a prepolymer of acrylic bone cement. The 4sPMMA with viscosity average molecular weight of about 45 kDa was synthesized via Atom Transfer Radical Polymerization method using Activators Regenerated by Electron Transfer (ARGET ATRP). In practical use, the fine powder of precipitated 4sPMMA was changed to rigid beads followed by making sheet and pulverizing. Proton nuclear magnetic resonance (HNMR), Fourier transform infrared (FTIR) spectra of 4sPMMA beads indicated the star structure of 4sPMMA with bromide end groups (C‐Br). Scanning electron microscopy (SEM) image of 4sPMMA beads showed their random shapes with size in the range of 10‐100 μm, no traces of residual metal catalysts (Cu and Sn) were detected by Energy Dispersive X‐Ray (EDX) analysizer equipped with SEM instrument. Bone cement from 4sPMMA beads had been prepared manually and curing in rectangular and cylindrical molds. The setting characterization results showed that 4sPMMA bone cements exhibited lower maximum temperature (63.9 °C), lower setting temperature (45.6 °C), than those required in ISO 5833:2002. Other properties of 4sPMMA bone cement, such as bending strength, bending modulus and setting time met the requirements of above ISO standard.